Analisis Pertumbuhan dan Nilai Perusahaan dalam Meningkatkan Laba Perusahaan Studi Kasus pada PT. Medco Energi International, Tbk. - Pardede, Robert Pius; Azhar, Ryza Mahadhika (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2007)
The purpose of this study is to know condition of company finance that is what will be growth condition, price of share and profitability company. In this research using ratio analysis that is for the growth use ratio of sale growth, for share price use ratio (Price Earning Ratio) PER and for ratio profitability use ratio of (Gross Profit Margin) GPM (Price to Book Value) PBV and. This research done by during five period by using data six period that is period 2000 until 2005. According to the researchâs result, it is possible to conclude that, monetary condition of Medco Energi International Tbk. PT as seen from the growth ratio can be considered as good due to the yearly increase. From the fair share ratio, Medco Energi International Tbkâ PT also can be categorized as good for the past five periodâs always on the increase. In addiction, companyâs profitability can be categorized as good although in former years, the company experienced a decrease but in 2005 however can regain its profit to the better level. Energi Mega Persada Tbk. PT according to the growth ratio also can be categorized as good because at former year the company experienced loss but significantly increase its profit years after from the fair share ratio, the company had just registered to the Jakarta Stock Exchance in 2003, so that it can be considered the companyâs fair share is not good enough to the decrease. Afterwards, as seen from the profitability, the company still lacks of quality due to the fluctualition and yearly decrease. However, companyâs monetary condition is influenced by work appearance of the company it self. Keywords : Selling, Share Price, PER and OPM